Cash-flow taxes in an international setting - Auerbach, A; Devereux, MP (American Economic Association, 2018)
This paper models the effects of cash-flow taxes on company profit which differ according to the location of the tax. The model incorporates a multinational producing and selling in two countries with three sources of economic rent, each in a different location: a fixed basic production factor (located with initial production), mobile managerial skill, and a fixed final production factor (located with consumption). In the general case, national governments face trade-offs in choosing between alternative taxes. In particular, a cash-flow tax on a source basis creates welfare-impairing distortions to production and consumption, but is partially incident on the owners of domestic production who may be non-resident. By contrast, a destination-based cash-flow tax does not distort behavior, but is incident only on domestic residents.